XXXV JEEP – 35th Conference on Phase Equilibria 2009
DOI: 10.1051/jeep/200900018
|View full text |Cite
|
Sign up to set email alerts
|

Comportement du Gonflement d’un Polymère Superabsorbant vis-à-vis de l’Eau dans un Sol Sableux

Abstract: RésuméCette étude concerne un polymère superabsorbant capable de retenir entre ces chaînes macromoléculaires 300 fois sa masse en eau. Cette intéressante attitude à se gonfler a été évaluée en fonction de plusieurs paramètres. Les résultats obtenus ont montré que le gonflement du polymère X3 dépend de la valeur du pH de la solution absorbée, mais l'influence de la température de la solution absorbée ne devient perceptible qu'à partir des valeurs supérieures à 40°C. L'exame n de l'effet de la présence des contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…It is also noteworthy that the WHC for black soil remained higher than that of arable soil. These results were consistent with those of Bahaj, et al [56] when incorporating increasing fraction of super-absorbent polymers in soil. Likewise, Sharma, et al [7] have previously demonstrated that soil mixed with pectin based-nanoparticle contributed to retain water for long time compare to reference native soil, providing plant growth favorable condition.…”
Section: Effect Of Pectin Powder On Garden Soil Water Holding Capacitsupporting
confidence: 92%
“…It is also noteworthy that the WHC for black soil remained higher than that of arable soil. These results were consistent with those of Bahaj, et al [56] when incorporating increasing fraction of super-absorbent polymers in soil. Likewise, Sharma, et al [7] have previously demonstrated that soil mixed with pectin based-nanoparticle contributed to retain water for long time compare to reference native soil, providing plant growth favorable condition.…”
Section: Effect Of Pectin Powder On Garden Soil Water Holding Capacitsupporting
confidence: 92%
“…Besides, their absorption capacity will depend on various physico-chemical parameters such as temperature, pH of the slurry, composition and concentration of the chemical elements in the tailings slurry, presence of salts and/or cations, etc. [18,[26][27][28]. The main objective of this paper is to assess the potential use of superabsorbent polymers (SAPs) for mine tailings slurry dewatering and to obtain densified tailings for surface storage.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, their absorption capacity will depend on various physico-chemical parameters such as temperature, pH of the slurry, composition and concentration of the chemical elements in the tailings slurry, presence of salts and/or cations, etc. [18,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%